Air disinfection and food preservation by ozone gas. Issue 1 (25th February 2019) - Nghi, Nguyen Hoang; Cuong, Le Cao; Dieu, Tran Vinh; Oanh, Doan Thi Yen
Abstract: Most food spoilage is the result of bio‐chemical reactions between microorganisms such as bacteria, funguses, molds, yests and food as carbon based organic matters. Food preservation by ozone gas slows or prevents this biochemical reaction. Ozone consumed for these reactions causes its reduction or decomposition. The amylaceous food (bread and other) and some kinds of fruits were chosen for research. The shape of the ozone reduction curves, its rate and half life time (HLT) reflects the rate of reaction between ozone and microorganism on food. The bacteriobiological and photographic analysis of the samples before and after ozone treatment show that ozone gas can kill or prevent the growth of funguses and mould so this gas can be effectively used to preserve the food.